Enhanced decolorization of methyl orange in aqueous solution using iron–carbon micro-electrolysis activation of sodium persulfate. (August 2017) - Li, Peng; Liu, Zhipeng; Wang, Xuegang; Guo, Yadan; Wang, Lizhang
Abstract: Reactivity of sodium persulfate (PS) in the decolorization of methyl orange (MO) in aqueous solution using an iron–carbon micro-electrolysis (ICE) method was investigated. The effects of sodium persulfate doses, pH, Fe-to-C mass ratios, initial MO concentration as well as the reaction temperature were comprehensively studied in batch experiments. The ICE-PS coupled process was more suitable for wide ranges of pH, initial MO concentration and reaction temperature, accompanied by the reduction of Fe compared ICE. The MO removal efficiency improved substantially by ICE-PS technique, 76.03% for ICE and 91.27% for ICE-PS at experimental conditions of pH 3.0, Fe-to-C mass ratio 3:1, PS addition 10 mM and initial MO concentration 0.61 mM. Furthermore, the biodegradability index (BI) dramatically increased from 0.26 to 0.65. The binary hydroxyl and sulfate radicals that non-selectively degrade MO to the derivatives with small molecules are ascribed to ICE-PS method as detected by the UV–vis spectra. The PS activation resource was Fe 2+ through the hydroxyl radical quenching reaction by the additive tert-butanol (TBA). This study provides an in-depth theoretical understanding of the development and wide commercial application of the ICE technology to refractory industrial dye wastewater treatment. Highlights: Decolorization of methyl orange by Fe-C micro-electrolysis with persulfate was tested. ICE-activated PS oxidation increased MO removal efficiency and BI of MO wastewater. ICE-PS is tolerant to wide range of pH, initial MO concentration, and temperature. Ferrous ions (Fe 2+ ) were the persulfate activation resource.